Effect of Blood Group on Ultrahigh Frequency Auditory Sensitivity - Prabhu,Prashanth (2018)
Abstract Introduction Individuals with blood group O are reported to have reduced otoacoustic emissions (OAEs) compared with individuals with different blood groups. Objective The present study attempted to determine if the blood group has any effect on high-frequency auditory sensitivity using ultrahigh-frequency audiometry and ultrahigh-frequency distortion product otoacoustic emissions (DPOAEs). Methods High-frequency thresholds and high-frequency DPOAEs were measured in 60 individuals with normal hearing and different blood groups. Results The results of the study showed that there was a significant reduction in DPOAE amplitude for individuals with blood group O compared with individuals with other blood groups. However, there was no significant difference in ultrahigh-frequency thresholds across the blood groups. Conclusion This reduction in OAE amplitude may be attributed to a lower number of healthy outer hair cells in individuals with blood group O. Further studies on larger groups of individuals are essential for a better generalization of the results.